Призначення та проведення митної експертизи при здійсненні митного контролю товарів - Бородін, Ігор Андрійович; Borodin, Ihor Andriyovych (Ірпінь, 2024)
У роботі досліджено процес митної експертизи при здійсненні митного контролю товарів, визначення її ролі та впливу на ефективність митної діяльності, а також розробка рекомендацій щодо вдосконалення практики проведення митної експертизи

The work examines the process of customs examination during the implementation of customs control of goods, determining its role and influence on the effectiveness of customs activities, as well as developing recommendations for improving the practice of conducting customs examination
Designation and conduct of customs expertise during customs control of goods
Keywords: митна експертиза; митний контроль; митні органи; митний кодекс; перевірка; customs examination; customs control; customs authorities; customs code; inspection